Strategic investment in the public sector for agricultural development - Seminario Duany, Alejandro (1993)
In this piece the author offers an analysis of public spending and suggests a number of possible policy changes in various areas. The main points of focus are the agriculture, transport and energy sectors. He also looks at the state's organizational setup and proposes alternatives that would enable coordination between the state and private investors, and open the way for investment projects.